(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The curricular proposals for professional development in foreign languages require the contribution of an interdisciplinary approach, because they deal with sociocultural constructs that are as important as language itself, in this context is not simply a vehicle for communication. In this sense, the objective of the study is to characterize the factors associated with professional training in a foreign language. The study considers that the interdisciplinary approach corresponds to the territorial approach, the use of the language versus the standard, the intervention of disciplines in professional training and the perspective of interdisciplinarity. The study applies a qualitative methodology corresponding to ethnography where oral communication with socio-cultural constructs is recorded in the everyday life, along with all sources of consultation that has allowed to build a model of professional development training in foreign languages. The use of the unstructured survey and in-depth interview has allowed to record the following results: the contribution of the interdisciplinary approach generates spaces to value the transdisciplinarity because any foreign language transcends, since it mobilizes and generates knowledge within open and closed territories. Languages represent dynamic processes that characterize the role of individuals within given contexts.